ANALYZING THE VALUE OF STUDENTS’ SOCIAL CARE CHARACTER IN THE EXTRACURRICULAR OF DANCE AT GRADE III OF SDN 4 PANJUNAN KUDUS - Ilma Lestiana Dewi; Fina Fakhriyah; Sekar Dwi Ardiant (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to describe and analyze the process of learning activities and the value of students' social care character that appeared during the extracurricular of dance at grade III SDN 4 Panjunan Kudus in the academic year 2020/2021. The method used in this research was a qualitative approach with the type of case study research to collect data and information in depth. Based on research results, the data obtained were (1) there was a process of learning activities starting from initial activities, core activities, and closing activities. The method used in the learning process was using the training method, in which the teacher provided examples of dance movements to students; then, all students followed by imitating the teacher's trainer movements. (2) The value of social care character appeared during the extracurricular activity in each indicator such as politeness, responsibility, and awareness. The results of observations obtained a score of 76.92% which was included in good category.